THE EFFECT OF MOTIVATION, EMOTIONAL INTELLIGENCE, AND ORGANIZATIONAL SUPPORT ON STUDENT PERFORMANCE (Study at the Department of Business Administration, University of Lampung Class of 2018) - ZA, Winda Hasdita; Djuardi, Dian Komarsyah; Saptiani, Fenny (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine the effect of motivation, emotional intelligence, and organizational support on student performance. This study uses a quantitative approach with the type of explanatory research. The sampling technique used is non-probably sampling with a saturated sampling technique, totaling 91 respondents from the 2018 Department of Business Administration, University of Lampung. The data were obtained from questionnaires distributed on a Likert scale. Data analysis in this study used multiple linear analysis, with the help of SPSS 25. This study shows that partially motivation has an insignificant effect on student performance, while emotional intelligence and organizational support have a significant influence on student performance. Simultaneously, motivation, emotional intelligence, and organizational support together have a significant influence on student performance at the 2018 Department of Business Administration, University of Lampung.